Formulas for failure? Were the Doha tariff formulas too ambitious for success? - Laborde Debucquet, David; Martin, Will (International Food Policy Research Institute, 2017)
In this chapter we outline the nature of the tariff-cutting rules and exceptions under consideration in the Doha Round and their implications for market access. Because they are very different in their details, we outline the agricultural proposals first and then those for nonagricultural market access. We focus on the December 2008 proposals that were under discussion when the negotiations collapsed and have not subsequently been modified, although negotiators could choose an alternative starting point if the negotiations were renegotiated. We consider the political costs of securing agreement under proportional tariff cuts and the key tariff-cutting approaches in the latest Doha proposals.